A Case Study of Parent–Child Interaction Therapy for the Treatment of Autism Spectrum Disorder. (December 2013) - Agazzi, Heather; Tan, Robin; Tan, Sim Yin
Comorbid disruptive behavior disorders occur in up to 80% of children with Autism Spectrum Disorder (ASD). Children with ASD often present as inattentive, noncompliant, and aggressive, making it difficult for them to engage in learning and social activities across settings. Parents and school staff report spending excessive time managing disruptive behaviors at the expense of engaging these children in meaningful skill development. Identifying effective interventions to decrease disruptive behaviors and increase positive skill development is of critical importance to improving outcomes for children with ASD. This case study presents the effectiveness of Parent–Child Interaction Therapy, an evidence-based intervention for young children with disruptive behavior, for addressing behavioral problems in a 7-year-old boy with ASD. Results suggested improvements in child compliance and decrease in disruptive behaviors. Further, parents increased their use of positive parenting strategies, including giving effective commands all of which serve to improve the parent–child relationship. Treatment implications for working with young children with ASD are discussed.